Hybridization in Canids—A Case Study of Pampas Fox (Lycalopex gymnocercus) and Domestic Dog (Canis lupus familiaris) Hybrid - Bruna Elenara Szynwelski; Rafael Kretschmer; Cristina Araujo Matzenbacher; Flávia Ferrari; Marcelo Meller Alievi; Thales Renato Ochotorena de Freitas (Animals, 2023)
Hybridization between species with different evolutionary trajectories can be a powerful threat to wildlife conservation. Anthropogenic activities, such as agriculture and livestock, have led to the degradation and loss of natural habitats for wildlife. Consequently, the incidence of interspecific hybridization between wild and domestic species has increased, although cases involving species of different genera are rare. In Vacaria, a Southern city in Brazil, a female canid with a strange phenotype, which had characteristics between the phenotype of the domestic dog (Canis familiaris) and that of the pampas fox (Lycalopex gymnocercus), was found. Our analysis suggests that the animal is a hybrid between a domestic dog and a pampas fox, but future studies are necessary to investigate additional cases of this hybridization in nature. This finding worries for the conservation of wild canids in South America, especially concerning Lycalopex species. Hybridization with the domestic dog may have harmful effects on pampas fox populations due to the potential for introgression and disease transmission by the domestic dog. Therefore, future studies to explore the consequences of hybridization on genetics, ecology, and behavior of wild populations will be essential to improve the conservation of this species.